Tuberculosis Correlation with Age and Gender in Kirkuk City-Iraq - Ibrahim Mohammed Saeed Hussein (Journal of Global Pharma Technology, 2018)
The study performed from 1st of January 2017 to 1st of April 2018. It was included (1042) patients data were collected from patients attending the Consultant Clinic for Chest and Respiratory Diseases in Kirkuk City. Results of the diagnostic procedure performed by direct microscopically technique using Ziehl-Neelsen (ZN) stain method for detecting Mycobacterium tuberculosis. The data showed that 523 of them were male and 519 of them were female patients. The examination results registered 83(7.96%) positive cases, 37(3.55%) of them were male whereas 46(4.41%) were female patients. According to the age group the results indicated that the age ranges of (15-24 years) showed the highest percentage of tuberculosis infection 18(21.68%) of the total positive cases, 7(8.43%) occurred in males and 11(13.25%) occurred in females. It was concluded that the highest proportion of positive TB cases were among the age group of (15-24 years) in both males and females..Keywords: Active PTB, Tuberculosis, Age & sex.